2022
DOI: 10.1155/2022/8294891
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Digital Marketing Communication Based on Intelligent Data Analysis

Abstract: In digital marketing, the core advantages of scientific and technological means such as artificial intelligence and big data analysis gradually appear and pay attention to them. This paper studies the accuracy of digital marketing and proposes an intelligent algorithm based on data analysis, which improves the effect of marketing communication. Through the combination of intelligent algorithms and big data analysis, the data are convincing. Through the comparison and improvement of intelligent algorithm logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the process of digital marketing, the integration of computer and communication technologies, innovative implementation of digital tools, interactive digital marketing research, and supporting market makers with data-driven marketing solutions is a new direction of future development. In the industrial market, some studies have put forward a method to evaluate the marketing effectiveness of industrial enterprises through correlation analysis, optimize communication effectiveness through digital marketing, and increase sales opportunities in the industrial market through statistical data analysis (Li, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the process of digital marketing, the integration of computer and communication technologies, innovative implementation of digital tools, interactive digital marketing research, and supporting market makers with data-driven marketing solutions is a new direction of future development. In the industrial market, some studies have put forward a method to evaluate the marketing effectiveness of industrial enterprises through correlation analysis, optimize communication effectiveness through digital marketing, and increase sales opportunities in the industrial market through statistical data analysis (Li, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The financial health and sustainability of the hospital are closely tied to the efficient management of specialist services, including patient scheduling, resource allocation, and revenue optimization. Moreover, specialist doctors play a key role in research and innovation within the medical field (Li, 2022). They often engage in cutting-edge research, clinical trials, and the development of new treatment protocols.…”
Section: Management Services As Core Business: a Perspective From Spe...mentioning
confidence: 99%
“…In DM, the main advantages of scientific and technological means, such as artificial intelligence and big data analysis appear, which improves marketing communication and thus enhances the social impact of DM. Purba et al (2020) found that digital financial products provided through fintech achieve happiness for respondents (Li, 2022). As for the banking sector, the authors emphasized (Rullis & Sloka, 2010;Daj & Chirca, 2009;Ebong & George, 2021) that financial institutions must implement new DM techniques (e.g., applications of digital innovations, such as digitizing business) to improve cost and deal with the crisis of confidence and thus promoting FI.…”
Section: Dmmentioning
confidence: 99%